A concept for a long-term scalable bioengineering model of primary care. (1st January 2012) - Maad, Soha; Dimitrov, Borislav D.; Fahey, Tom
We present a concept for development of a unified bioengineering framework that consolidates efforts in extending the geographical boundaries and outreach of primary care in Ireland and ensure its long-term scalability. This framework encompasses infrastructures, devices, systems, techniques, materials, engineering practices and socio-technical set-ups for improved access, safety and quality of care at national and global levels. In particular, we address the development of special purpose solutions, technologies and devices for healthcare from a bioengineering perspective, within the wider healthcare and biotechnology agendas in Ireland.